A reformulated nonlinear model to solve the facility layout problem. Issue 4 (3rd April 2019) - Vázquez-Román, Richart; Díaz-Ovalle, Christian O.; Jung, Seungho; Castillo-Borja, Florianne
Abstract: The facility layout problem is fundamental during the plant design. The solution of this problem has required strategies that become in numerical challenges. One of them is the exact method, which finds optimal distributions for facility layout, as demonstrated in the linear and disjunctive models. Both models are distinguished by a high quantity of nonoverlapping constraints. In contrast, a nonlinear model was formulated with low number of constraints, but it has been solved by genetic algorithms. Herein, that model is reformulated to a MINLP (mixed integer nonlinear programing) problem. The solution was possible using a visual interface linked to GAMS (General Algebraic Modeling System). Three case studies were solved to compare them. The reformulated model reached feasible solutions, and its computational time and binary variables were lower than those of the others. This suggests that the reformulated model can be extended to solve topics about process safety.